„Niemiłe przebudzenie” – Wielka Brytania wobec chińskiego ruchu na rzecz odzyskania praw do kolei (1905–1911) - Nowikiewicz, Mateusz (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2022)
The purpose of this article is to present a certain episode from the history of railroads in China – the reaction of diplomats and British business entities to the actions of the Railway Rights Recovery Movement (shouhui luquan yundong) during the final years of the Qing dynasty rule. First, a broader historical context is outlined, and within it the earliest at tempts to establish railway infrastructure in the Middle Kingdom and Chinese policy on this matter.
Keywords: regional studies; region; Silesia; Poland; Czech Republic; Germany; regional journal; historical journal